Protein Synthesis by Human Blood Platelets after Accumulation of Leucine and Arginine - Boullin, D.J; Votavova, M; Green, A.R (Thrombosis and Haemostasis, 1972)
Human blood platelets resuspended in calcium-free Krebs solution accumulated radioactive L-leucine and L-arginine. The tissue/medium concentration ratio (Ci/Co) was greater than 10:1 when Co was 10–7 M or lower. Accumulation was inhibited by incubation at 4° C, the presence of metabolic inhibitors or platelet soniñcation at the beginning of the experiment. It is considered that these compounds are accumulated by energy-dependent processes against a concentration gradient.In the presence of 19 other amino acids accumulation of leucine or arginine was greatly reduced. Under these conditions some incorporation of radioactivity into proteins occurred. However, incorporation was small. Both compounds were incorporated similarly despite the fact that arginine is metabolized to ornithine, whilst leucine has no detectable metabolites. This fact is discussed in relation to the possible physiological significance of platelet protein synthesis.